2015
DOI: 10.1155/2015/576743
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Intravenous Leiomyomatosis with Cardiac Extension: Radiologic Assessment with Surgical and Pathologic Correlation

Abstract: We present the computed tomography (CT) and magnetic resonance (MR) imaging findings of a 71-year-old woman with a cardiac extension of intravenous leiomyoma (IVL) that arose from the uterus, extended to the inferior vena cava (IVC), and reached the right ventricle through the right ovarian vein. Radiologic-pathologic correlation showed that the intravascular cord-like mass originating from the IVC and extending to the right ventricle was composed of degenerated smooth muscle cells with a number of large vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Previous studies have reported these tumors often stain positively for both estrogen and progesterone receptors [8][9][10][11][12]. Our patient's cardiac mass was 95% and 20% immuno-reactive for estrogen and progesterone, respectively, consistent with a uterine origin.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Previous studies have reported these tumors often stain positively for both estrogen and progesterone receptors [8][9][10][11][12]. Our patient's cardiac mass was 95% and 20% immuno-reactive for estrogen and progesterone, respectively, consistent with a uterine origin.…”
Section: Resultssupporting
confidence: 49%
“…However, this study found no significant relationship between the type of primary surgery and BML diagnosis with respect to timing of surgery or site of metastasis. Three out of the four other recorded cases of BML to the heart had multiple lung metastases [7][8][9][10][11][12]. In these case reports, BML was found in the right atrium, interventricular septum, tricuspid valve and right ventricle [8].…”
Section: Resultsmentioning
confidence: 97%
“…This is followed by CT with angiography, which gives detailed information regarding the complete path of the lesion. This can be seen as worm-like tumor extension through the ovarian or uterine vein, into the IVC, and ultimately into the right heart [ 8 ]. Complete surgical resection, when possible, is the treatment of choice to prevent a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main theories which attempt to explain the etiology of uterine IVL: mural origin of the tumor from the venous walls and direct vascular invasion by a primary tumor arising from an uterine leiomyoma [ 10 ]; the second theory is favored in the literature for the following reasons: (a) patients have a history of uterine myoma or have undergone myomectomy or hysterectomy; (b) tumor bases were often connected to the uterine wall on pathological and imaging examination; (c) tumor cells tested positive for estrogen- and progesterone-receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%